2020
DOI: 10.1080/16184742.2020.1777453
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity, critical masses, and organizational problems of non-profit sport clubs

Abstract: Research question: This study examines the effect of board gender diversity and a critical mass of women on the board on organizational problems of non-profit sport clubs. It relies on theories from social categorization and information/decisionmaking perspectives and on critical mass theory. Research methods: Four waves of data from a German sport club panel (2009)(2010)(2011)(2012)(2013)(2014)(2015); n = 6504) are used which allow analyzing causal effects with lagged variables. Gender diversity was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 56 publications
1
29
0
6
Order By: Relevance
“…Two competing theoretical perspectives, social categorization perspective and the information/decision-making perspective, have guided most of the studies on gender and organizational outcomes (Lee and Cunningham 2019;Nowy and Breuer 2019;Wicker et al 2020).…”
Section: Board Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Two competing theoretical perspectives, social categorization perspective and the information/decision-making perspective, have guided most of the studies on gender and organizational outcomes (Lee and Cunningham 2019;Nowy and Breuer 2019;Wicker et al 2020).…”
Section: Board Diversitymentioning
confidence: 99%
“…Previous studies have cited contradicting results on whether diversity has a positive or negative result on organizational results in (sport) organizations (Dula et al 2020;Lee and Cunningham 2019;Milliken and Martins 1996;Wicker et al 2020). For instance, studies have found gender diversity to decrease organizational problems (Wicker and Breuer 2013;Wicker et al 2012Wicker et al , 2020 and increase organizational outcomes owing to, for instance, learning from others, role modelling, idea generation (Cunningham 2008), and higher decision-making and problem-solving capabilities (Lee and Cunningham 2019).…”
Section: Board Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, empirical studies show that members of sports clubs do not come equally from all parts of the population. Women, older adults and low wage earners are less likely to be members of clubs or volunteers (Hartmann-Tews, 2006;Haut and Emrich, 2011;Nobis and El-Kayed, 2019;Wicker et al, 2020). Furthermore, the following findings are often cited: (a) the underrepresentation of firstand second-generation immigrants in sports clubs is more prevalent in female than in male sports; (b) immigrant male adolescents report membership in clubs just as much as their non-immigrants peers; (c) participation rates of firstand second-generation immigrants are higher in football and martial arts than in other sports; and (d) other sport activities (e.g.…”
Section: Sports Clubs and The Politics Of Belongingmentioning
confidence: 99%
“…In the leisure sports sector, only a few studies have investigated the impact of board gender diversity or critical masses of women on economic sustainability. Sport organizations with a critical mass of three women on the board were found to have fewer financial problems [15] and generate higher revenues [16].…”
Section: Introductionmentioning
confidence: 99%